Environmental, Social and Governance and Sustainable Development in Healthcare - Leung, Tiffany Cheng Han.; Chiu, Wang-Kin.; You, Cindy Shi-Xiang.; Fong, Ben Yuk Fai. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book applies environmental, social and governance (ESG) to issues of sustainable development in healthcare. ESG reporting has been widely used for some time in the business industry to show the economic, social and environmental responsibilities of companies that aim to achieve superior ESG performance for lower risk, more accountability and transparency. Moreover, public-listed companies in healthcare have been growing in significant numbers in recent years. The application or practice of ESG in healthcare has become a growing trend for these large organisations looking to demonstrate their strengths in areas of financing, operations, sustainability and social responsibilities. Such an approach is essential not only for the long-term development of the companies but also for services delivered by healthcare practitioners. Equally, the implications to Sustainable Development Goal (SDG) 3 is relevant to healthcare worldwide with a growing ageing population, which has led to a great burden of care in many countries, particularly in the public sector. The potential development and expansion in private healthcare services, accelerated by technology advancement, has demanded a new paradigm in the healthcare industry, particularly in business, service delivery and policy. The book examines this paradigm through health in all policies, ESG and SDG 3 objectives, research, training and practice. It is relevant to graduate students and scholars working in areas relating to health, business and the SDGs and is also useful to policymakers and practitioners in healthcare. .
Introduction -- Environmental, Social and Governance (ESG) in the Business Industry -- Sustainable Development Goal 3 in Healthcare -- ESG Application in Sustainable Development of the Healthcare Industry -- New Paradigms in the Business of Healthcare -- Environmental, Social, and Governance (ESG) Promotion to Different Stakeholder Groups -- Recent Trends of Research and Education in ESG and Sustainability.
Keywords: Age distribution (Demography).; Medical care; Sustainability; Political planning; Business; Asia; Aging Population; Health Care; Sustainability; Public Policy; Asian Business